DO INFLATION, INTEREST RATE AND COST OF RENTING AFFECT THE PRICE OF TERRACE HOUSES IN PENANG? - Zainuddin, Zaemah; Mohd Yusof, Rosylin (PLANNING MALAYSIA, 2020)
In Malaysia, the housing ownership is reported to decrease from 85% in 1999 to 72.5% in 2010. This is due to the outstripped increase of house price over the income level and the unstable economic situation which creates unaffordability to own a house for many people. Therefore, the main objective of this study is to examine whether the price of terrace houses in Penang is being affected with fundamental factors such as inflation, interest rates and the cost of renting. This study uses multivariate regression analysis with quarterly data of terrace house prices (HPI terrace house in Penang), inflation (CPI) and interest rate (mortgage rates) from 2009: Q1 to 2016: Q4. Evidently, the cost of renting terrace houses in Penang does not have any impact on the price of terrace houses and the stable movement of cost of renting indicates that the growth of rental rate is at acceptable price for middle income earners.